2013
DOI: 10.5897/ajpp2013.3571
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of sildenafil against cysteamine induced duodenal ulcer in Wistar rats

Abstract: The aim of the current study was to investigate the possible protective effect of sildenafil (SIL) on cysteamine induced peptic ulcer in Wistar rats. Rats were randomly divided into five groups; six animals each. Normal control group; in which animals received an aqueous solution of Tween 80 (1 ml/kg) as a vehicle, two doses orally at an interval of 4 h. SIL group, in which animals received 25 mg/kg SIL orally 30 min before vehicle administration. Cysteamine group; in which duodenal ulceration was induced by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…This was consistent that compound 5 was triterpenoids with five six-membered ring with hydroxymethyl group δH 3.19 (1H, dd, J = 11.5; 5.0 Hz, H-3), olefinic proton δH 5.27 (1H, t, J = 7.5Hz, H-12) ( Table-5). The presence of 30 carbon atoms with 5 methine carbons, 10 methylene carbons, 7 methyl cacbons and 7 quaternary carbons was confirmed by 13 C NMR and DEPT spectra. The difference observed between compounds 4 and 5 was that of methyl group at position 29.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…This was consistent that compound 5 was triterpenoids with five six-membered ring with hydroxymethyl group δH 3.19 (1H, dd, J = 11.5; 5.0 Hz, H-3), olefinic proton δH 5.27 (1H, t, J = 7.5Hz, H-12) ( Table-5). The presence of 30 carbon atoms with 5 methine carbons, 10 methylene carbons, 7 methyl cacbons and 7 quaternary carbons was confirmed by 13 C NMR and DEPT spectra. The difference observed between compounds 4 and 5 was that of methyl group at position 29.…”
Section: Resultsmentioning
confidence: 87%
“…Compound 3 gave a molecular formula of C17H34O2 based on the ESI-MS spectrum, revealing a molecular ion peak at m/z 271,12 [M+H] + . In 1 H NMR spectrum, the resonance signal of methylene group at δH 2.33 (2H, t, J = 7.5 Hz, H-2) directly attached to the carbonyl group corresponding to the carbon signal at δC 33.9 (C -2) in 13 C NMR spectrum and also showed another methylene group, was adjacent to this group at δH 1.64 (2H, quartet, H-3). The presence of a carbonyl group of acid was easily recognized in 13 C NMR spectrum based on resonant signal at δC 179.1 (C-1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Gastric and duodenal anti-ulcer activity of ethylacetate fraction from Sanchezia nobilis Hook.F. was evaluated on cysteamine induced gastric and duodenal ulcer models in adult Wistar albino rats with two oral doses of cysteamine (400 mg/kg) at an interval of 4 h. 10,11 Cysteamine hydrochloride has been found to be the most potent agent for inducing duodenal ulcer, and cysteamine induced duodenal ulcer in animals is now used to study the antiulcer activity of drugs. The cysteamine used in experimental studies has been found to concentrate in the duodenum.…”
Section: Evaluation Of Anti-ulcer Activitymentioning
confidence: 99%